2000
DOI: 10.11606/issn.2176-7262.v33i3p219-231
|View full text |Cite
|
Sign up to set email alerts
|

Transplante de medula óssea em anemias aplásticas

Abstract: As aplasias medulares compreendem entidades clínicas adquiridas e congênitas que, através de mecanismos distintos, determinam redução acentuada da celularidade da medula óssea em uma ou mais linhagens, sem infiltração neoplásica ou fibrose. A intensidade das citopenias, no sangue periférico, confere a gravidade da doença, particularmente quando relacionada à trombocitopenia e à neutropenia. A Anemia Aplástica Severa (AAS) adquirida é a entidade mais freqüente deste grupo e seu tratamento consiste em medidas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
7

Year Published

2005
2005
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
1
0
7
Order By: Relevance
“…At the end of the 1980's, the Seattle group started using the association of CY and ATG, which is currently the most commonly used regimen, with an overall reduction of rejection rates in less transfused patients (12,13,18,19). In Brazil, a pilot study showed that the association of BU and CY was also feasible in heavily transfused patients (13), with a rejection rate of 9% and an overall survival of 70% (8). Since that study, BU-CY has been used by many Brazilian transplant centers due to its lower cost than ATG-CY.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 1980's, the Seattle group started using the association of CY and ATG, which is currently the most commonly used regimen, with an overall reduction of rejection rates in less transfused patients (12,13,18,19). In Brazil, a pilot study showed that the association of BU and CY was also feasible in heavily transfused patients (13), with a rejection rate of 9% and an overall survival of 70% (8). Since that study, BU-CY has been used by many Brazilian transplant centers due to its lower cost than ATG-CY.…”
Section: Discussionmentioning
confidence: 99%
“…Estas complicações já estão amplamente documentadas na literatura médica nacional e internacional (1)(2)(3)(4) .…”
Section: Introductionunclassified
“…Essa consequência pode ser devido o uso de algumas drogas e agentes químicos (agentes citotóxicos, cloranfenicol, anti-inflamatórios não esteroidais, antiepiléticos, sais de ouro, benzeno), exposições a pesticidas, infecções virais ativas (Epstein Barr, vírus da hepatite, parvovírus, vírus da imunodeficiência humana), neoplasias hematológicas, invasões medulares de neoplasias não hematológicas, doenças sistêmicas, doenças autoimunes e exposições à radiação (GAMAN et al, 2009;PASQUINI, 2000;TELES et al, 2002).…”
Section: Anemia Aplástica E Sua Etiopatogeniaunclassified
“…Esses pacientes recebem uma combinação de Globulina anti-timócito seguido por Ciclosporina A (GAMAN et al, 2009;SCHEINBERG et al, 2012). Estas drogas apresentam vários efeitos colaterais como: hipertensão; hiperplasia gengival; tremor; nefrotoxicidade, sendo que muitos pacientes não respondem adequadamente as terapias imunossupressoras (PASQUINI, 2000;SANDOZ, 1998).…”
Section: Anemia Aplástica E Sua Etiopatogeniaunclassified
See 1 more Smart Citation